BS EN ISO 10893-1 AMD1. Non-destructive testing of steel tubes. Part 1. Automated electromagnetic testing of seamless and welded (except submerged arc-welded) steel tubes for the verification of hydraulic leaktightness (27th August 2019) - British Standards Institution,
No abstract available